K(+)-p-nitrophenylphosphatase activity in rat brain and liver - Ďurfinová, M; Brechtlová, M; Líska, B; Barošková, Z (Physiological research, 2009)
K(+)-p-nitrophenylphosphatase (K(+)pNPPase) is the enzyme, which is considered to be involved in K(+)-dependent hydrolysis of the phosphoenzyme in the reaction cycle of Na(+), K(+)ATPase. The aim of our present study was to characterize some features of K(+)pNPPase in homogenates of the rat brain and liver. We determined p-nitrophenylphosphatase (pNPPase) activity in the presence of various ion combinations (Mg(2+)+ K(+), Mg(2+), K(+)). We found a higher total pNPPase activity in the brain (0.8+/-0.079 nkat/mg protein) than in the liver (0.08+/-0.01 nkat/mg protein). Contrary to the liver, the main part of the total brain activity was K(+)-dependent. The activity of K(+)pNPPase was significantly higher in cerebral cortex homogenates (0.86+/-0.073 nkat/mg protein) in comparison to those of the whole brain (0.57+/-0.075 nkat/mg protein). The specific K(+)pNPPase activity was two times higher in the isolated pellet fraction (0.911+/-0.07 nkat/mg protein), rich in synaptosomes, compared to the whole brain homogenate (0.57+/-0.075 nkat/mg protein). Our results demonstrate the high activity of K(+)pNPPase in the brain tissue and its distribution mainly into the pellet fraction, what might indicate a possible role of K(+)pNPPase in specific structures of the brain, e.g. in synaptosomes.
Keywords: Magnesium; Cerebral Cortex; Potassium; mozková kůra; draslík; synaptozomy; Rats; Male; 4-Nitrophenylphosphatase; 4-nitrofenylfosfatasa; játra; Brain; mozek; Calcium; Synaptosomes; potkani Wistar; vápník; Liver; mužské pohlaví; Rats, Wistar; Animals; hořčík; zvířata; krysa rodu Rattus